PERANCANGAN TANGKI SIMULASI REAKTOR UNTUK UNTAI UJI SISTEM KENDALI REAKTOR RISET - Suwardiyono Suwardiyono; Puji Santosa; Muhammad Awwaluddin (Jurnal Perangkat Nuklir, 2012)
A DESIGN OF REACTOR SIMULATION TANK FOR CONTROL SYSTEM STRAND TEST OF RESEARCH REACTOR. A design of reactor simulation tank for control strand test of research reactor has been performed. Basic calculations of this design are to have the cooling water flow rate of 431 liters / hour with water outlet temperature 42 oC and water inlet temperature 40 oC. The reactor core tank in the simulation is made of 304 stainless steel plate with 3 mm thickness. Its cooling water volume is 862 liter in which its inside (Di) and outside (Do) diameter are 950 mm and 956 mm respectively. The tank height (T) is 1582 mm, and its bottom lid radius (R) is 0.8 D. The tank insulation materials are made of silica board sheet with 50 mm thickness using 0.2 mm aluminum plate jacket. From the calculation can be concluded that the tank is very safe against the possibility of cutting-down, breaking-up, and splitting-up because the thickness of stainless steel 303 calculated in the design (t) is 3 mm which is greater than its limit thickness required for cutting-down (tp) 0.248 mm, breaking-up (tb) 0.155 mm, and splitting-up (tu) 0.745 mm. The 50 mm thickness of silica board sheet using 0.2 mm aluminum jacket will give the heat loss around 0.53% so that the silica board can be used for the thermal insulation of the reactor simulation tank for control system test of research reactor.  PERANCANGAN TANGKI SIMULASI REAKTOR UNTUK UNTAI UJI SISTEM KENDALI REAKTOR RISET. Telah dilakukan perancangan tangki simulasi reaktor untai uji sistem kendali reaktor riset.Basis perhitungan pada perancangan ini adalah laju alir air pendingin 431 liter/jam dengan suhu air pedingin keluar 42 0C dan suhu air masuk 40 0C Tangki simulasi teras reaktor riset tersebut dibuat menggunakan bahan plat stainless steel 304 dengan tebal 3 mm, ukuran isi volume air pendingin 862 liter, diameter dalam (Di) 950 mm, diameter luar (Do) 956 mm, tinggi tangki (T) 1.582 mm dan jari-jari tutup bawah tangki (R) 0,8 D. Bahan isolasi tangki menggunakan silica board tebal 50 mm dengan jaket plat aluminium 0,2 mm. Dari hasil perhitungan apat disimpulkan bahwa tangki tersebut sangat aman digunakan karena tahan terhadap kemungkinan putus, terbelah dan pecah. Hal ini diperoleh dari tebal plat stainless steel 303 (t) 3 mm > tebal plat yang diperlukan agar tidak putus (tp) 0,248 mm, agar tidak terbelah (tb) 0,155 mm dan agar tidak pecah (tu) 0,745 mm. Demikian pula dari hasil perhitungan bahwa bahan isolasi silica board dengan tebal 50 mm dan jaket alumunium tebal 0,2 mm tersebut panas yang hilang hanya sekitar 0,53 %, maka isolator jenis silica board sagat bagus digunakan untuk isolator panas pada tangki simulasi teras reaktor untai uji sistem kendali reaktor riset.